Determination of Cooper pairs and Majorana fermions currents ratio in dc SQUID with topologically nontrivial barriers - Rahmonov, I.R.; Shukrinov, Yu.M.; Dawood, R.; Samman, H. El (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
We present the results of numerical study of the phase dynamics of the dc SQUID with topologically trivial and nontrivial barriers. In our calculations we take into account two components of superconducting current, Cooper pairs (2π periodic) and Majorana fermions (4π periodic) currents. Magnetic field dependence of return current is presented. The qualitative behavior of this dependence is explained. We show that in case of twocomponent superconducting current the periodicity of magnetic field dependence of return current displaced by Cooper pairs and Majorana fermion ratio over the magnetic field. This effect makes possible the experimental determination of ratio of Cooper pairs and Majorana fermions currents.